2016
DOI: 10.1177/0146167216665096
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Identity Safety Cue Transfers

Abstract: Traditionally, researchers have focused on identity-congruent safety cues such as the effect of gender diversity awards on women's sense of inclusion in organizations. The present studies investigate, for the first time, whether identity safety cues (e.g., organizational diversity structures) aimed at one stigmatized group transfer via perceptions of the organization's ideology (social dominance orientation), resulting in identity safety for individuals with stigmatized identities incongruent with the cue. Acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 36 publications
2
105
3
Order By: Relevance
“…This study suggests that diversity initiatives and messages may not make the interview process feel less threatening for Latino men and may ironically create more concerns about being liked and treated fairly. Although this seems to contrast with prior work on the effect of diversity initiatives on anticipated belongingness and fair treatment (Chaney et al., ; Purdie‐Vaughns et al., ), it is not necessarily contradictory. For example, it is possible that other minority groups (e.g., White women, Black men and women) are more positively affected by messages about diversity.…”
Section: Signaling Consequences Of Organizational Diversity Initiativescontrasting
confidence: 80%
See 3 more Smart Citations
“…This study suggests that diversity initiatives and messages may not make the interview process feel less threatening for Latino men and may ironically create more concerns about being liked and treated fairly. Although this seems to contrast with prior work on the effect of diversity initiatives on anticipated belongingness and fair treatment (Chaney et al., ; Purdie‐Vaughns et al., ), it is not necessarily contradictory. For example, it is possible that other minority groups (e.g., White women, Black men and women) are more positively affected by messages about diversity.…”
Section: Signaling Consequences Of Organizational Diversity Initiativescontrasting
confidence: 80%
“…Among these participants, brochures featuring either multicultural messages or photos of diverse employees led to higher attraction to the company and greater anticipated belonging at the company than brochures with neither. In another set of studies, White women and men of color reported higher levels of anticipated belonging in the presence (vs. absence) of diversity initiatives (Chaney et al., ). Dover et al.…”
Section: Signaling Consequences Of Organizational Diversity Initiativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some emerging experimental evidence suggests that interventions designed to signal inclusivity toward members of 1 stigmatized group (eg, LGBTQ youth) may lead members of other stigmatized groups to feel safe as well (eg, racial minority youth). 73 Therefore, interventions designed to promote LGBTQ inclusivity may enhance feelings of safety and belonging among all youth.…”
Section: Interventionmentioning
confidence: 99%